The Role And Role Of The Media In The Formation Of The Natural Scientific World Of Preschool Children - et. al., Umida Lutfullayevna Yoziyeva, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article discusses the role and place of the media in shaping the worldview of preschool children, as well as the content of media laws adopted in the Republic of Uzbekistan and the history of the development of natural sciences in Central Asia. Frankly, young people with a broad outlook will develop the country, increase the welfare of the country, and put the interests of the people above their own. Especially young people with a natural-scientific outlook will be intellectually gifted, thirsty for knowledge, inquisitive, well-versed in the basics of science. According to this, man creates a whole system of views and ideas about the universe and man. Most importantly, it answers questions such as a person's attitude to the world, his place in the world, his essence, direction in life, self-awareness. After all, the basis of philosophy is to create a worldview that is conducive to common sense and its development. To do this, one must first have a thorough knowledge.